2021
DOI: 10.1111/ijac.13784
|View full text |Cite
|
Sign up to set email alerts
|

Rheology and processing of UV‐curable textured alumina inks for additive manufacturing

Abstract: A UV‐curable resin containing alumina (Al2O3) powder and platelets was developed and characterized using a proof‐of concept tape‐casting system and trialed on a commercially available 3D‐printing platform (Admatec Admaflex 130). The influence of solids loading and solids platelet fraction on resin viscosity and depth of cure was investigated. Resins containing up to 40 vol% solids loading at platelet fractions up to 50% were found to have sufficiently low viscosity for tape casting and cure depths ranging from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Combined with the almost 10% increase in shrinkage in the z‐direction over the x and y‐direction shown in Table 4, suggests that the majority of channels being formed for burnt off gasses to escape is occurring between layers. The increased shrinkage in the z‐dimension is a common phenomenon in DLP printing that is reported in literature 16,33,41,42 . It can also be suggested that the channels collapse during the sintering processes, leading to the increased shrinkage in the z‐direction.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…Combined with the almost 10% increase in shrinkage in the z‐direction over the x and y‐direction shown in Table 4, suggests that the majority of channels being formed for burnt off gasses to escape is occurring between layers. The increased shrinkage in the z‐dimension is a common phenomenon in DLP printing that is reported in literature 16,33,41,42 . It can also be suggested that the channels collapse during the sintering processes, leading to the increased shrinkage in the z‐direction.…”
Section: Resultsmentioning
confidence: 73%
“…The increased shrinkage in the z-dimension is a common phenomenon in DLP printing that is reported in literature. 16,33,41,42 It can also be suggested that the channels collapse during the sintering processes, leading to the increased shrinkage in the zdirection. In Figure 7A beyond 10 mm in the x or y-direction.…”
Section: Cuboid and Cylinder Delaminatingmentioning
confidence: 99%